Influence of Mangosteen Pericarp (MP) in Coagulation Treatment and Membrane Fouling - Qi, Low Aik; Mazrul Nizam, Abu Seman; Asmadi, Ali (Italian Association of Chemical Engineering - AIDIC, 2017)
The available conventional water treatment processes has not readily met the drinking water quality. The chemical used in treatment process will produce by-product that might affect the treated water quality. In light of this research was carried out to investigate the effectiveness of Mangosteen Pericarp (MP) powder as a new coagulant aid in coagulation and ultrafiltration hybrid process. This was done by using doses of 0.05 g/L, 0.10 g/L, 0.15 g/L, 0.20 g/L, 0.25 g/L, and 0.30 g/L of the MP powder together with aluminum sulphate (Alum) as coagulant. The turbidity, UV254 and pH were determined for all the samples. MP is highly potential in improving the turbidity removal efficiency during coagulation process. It was found that most significant improvement of the turbidity removal efficiency was recorded near to neutral pH which is pH 6 and pH 8 with 0.3 g MP to harvest 97.9 % and 98.6 % removal efficiency. The optimum has recorded at 0.2 g Mp with pH 10 to obtain 99.5 % turbidity removal efficiency. In the presence of Humic Acid (HA), pH was the major factor in enhancing the turbidity and UV254 removal where at pH 10 with 0.2 g MP can capture up to 99.6 % of turbidity and 97.6 % of UV254. The favourable micro micro-intercoiled texture of MP enable to entrap the impurities in the coagulation process in order to sustain the membrane flux by reducing the membrane fouling.